Investigation into the limits of perturbation theory at low Q2 using HERA deep inelastic scattering data - Abt, I; Cooper-Sarkar, AM; Foster, B; Myronenko, V; Wichmann, K; Wing, M (American Physical Society, 2017)
A phenomenological study of the final combined HERA data on inclusive deep inelastic scattering has been performed. The data are presented and investigated for a kinematic range extending from values of the four-momentum transfer, Q2, above 104 GeV2 down to the lowest values observable at HERA of Q2=0.045 GeV2 and Bjorken x, xBj=6×10-7. The data are well described by fits based on perturbative quantum chromodynamics (QCD) using collinear factorisation and evolution of the parton densities encompassed in the Dokshitzer-Gribov-Lipatov-Altarelli-Parisi formalism from the highest Q2 down to Q2 of a few GeV2. The Regge formalism with the soft Pomeron pole can describe the data up to Q2≈0.65 GeV2. The complete data set can be described by a new fit using the Abramowicz-Levin-Levy-Maor parametrization. The region between the Regge and the perturbative QCD regimes is of particular interest.